PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE BERBANTUAN MEDIA KOMIK TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS V SEKOLAH DASAR PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Saraswati, Presti; Rika Perdana, Dayu; Fernando Rizqi, Yoga; Nurwahidin, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking is an essential ability in Pancasila Education. However, the critical thinking ability of fifth-grade students at SD Negeri 6 Metro Timur remains low. This condition is influenced by students’ limited cognitive abilities and the learning process, which is dominated by the use of less varied instructional models and media. This study aims to examine the effect of the Think Pair Share learning model assisted by comic media on students’ critical thinking ability. This study employed a quantitative approach with a quasi experimental design and a nonequivalent control group design. The population consisted of 39 fifth-grade students divided into an experimental class and a control class. Data were collected through tests, observations, interviews, and documentation. Data were analyzed using a simple linear regression test. The results indicate that the Think Pair Share learning model assisted by comic media has a significant effect on the critical thinking ability of fifth-grade students at SD Negeri 6 Metro Timur in Pancasila Education.